Clinical outcome and risk factor predictive for failure of autologous PRP injections for low-to-moderate knee osteoarthritis. (24th June 2021) - Alessio-Mazzola, Mattia; Lovisolo, Stefano; Sonzogni, Beatrice; Capello, Andrea Giorgio; Repetto, Ilaria; Formica, Matteo; Felli, Lamberto
Purpose: To report the 5-year clinical efficacy of PRP intra articular injections in knee osteoarthritis (OA) and to investigate the risk factors predictive for treatment failure and poor clinical outcome. Methods: We retrospectively evaluated 118 patients treated for low to moderate knee OA demonstrated by X-Ray and magnetic resonance imaging (MRI) with autologous PRP injection from 2014 to 2018 with a mean 51.1 ± 14.8 (range 29 to 89) months follow-up. All the patients were evaluated with Lysholm and WOMAC score. The role of Kellgren Lawrence (KL) grade, patello-femoral (PF) degeneration, age, body mass index (BMI), relevant comorbilities, smoking status, gender, previous surgery or conservative measures were analyzed with univariate and multivariate analysis. Results: There was a significant improvement of all outcome measures at final follow-up and high satisfaction rate (79.7%). The overall failure rate was of 15.3% after a mean of 57.7 ± 15.1 (range 33 to 85) months. The BMI and the KL grade were identified as significant independent risk factor related to failure of autologous PRP injection. Patients under 60 reported significantly higher Tegner activity scale ( p = 0.032) at final follow-up. Patients with KL grade 3 and patients with PF MRI-KL grade 3 had significantly lower Lysholm scores ( p = 0.026 and p = 0.042 respectively) at final assessment. Younger patients with lower BMI and lower grade of radiographic OA had significantly longer therapeutic benefit ( p < 0.05). Conclusion: Intra articular PRP injections led to a significant clinical improvement in middle-aged adults with a low to moderate knee OA. BMI and high KL grade have been identified as significant risk factors predictive for failure at mid-term follow-up.